AN ANALYSIS OF BANNED FIXED-DOSE COMBINATIONS IN INDIA - PATEL, SHRUTI; SHAH, SAMIDH; DESAI, CHETNA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to analyze the nonsteroidal anti-inflammatory drugs (NSAIDs) and respiratory fixed-dose combinations (FDCs) recently banned in India. Methods: This observational study was conducted at the Department of Pharmacology, B. J. Medical College, Ahmedabad, Gujarat. The data were collected from the report on the banned FDCs submitted by the drug technical advisory board subcommittee. Total 195 FDCs belonging to NSAIDs (33) and respiratory group (162) were assessed for class, number of active pharmacological ingredients, formulations, indications, and reasons for banning. Results: The mean number of drugs in FDCs of NSAIDs was 2.6, while in respiratory FDCs, it was 3.6. The most common NSAID formulation was uncoated tablet (15, 30%) while it was syrup in respiratory (49, 30%). The most common reasons for banning these FDCs were safety concerns (153, 78.4%), followed by mismatched pharmacodynamics in respiratory FDCs and mismatched pharmacokinetics in NSAIDs FDCs. The NSAIDs FDCs were marketed for pain (70%) while respiratory FDCs were marketed for cough and cold (62%). Most common NSAIDs FDCs contained NSAID with NSAID (18%), while in respiratory FDCs combinations of a cough suppressant, expectorant, and soothing agents (10%) were present. Conclusion: Evaluation of FDCs is essential to prevent the marketing of irrational FDCs.